Islamic banking and the question of secularism in Nigeria (2016)
Since the introduction of Islamic banking in Nigeria, the importance of secularism has been the object of discussion, with the general belief by a large number of people that Islamic banking will Islamise Nigeria and disrupt its secularity. It is against this backdrop that this paper discusses the issue of secularism in relation to Islamic banking in Nigeria. Specifically, it examines the role of religion particularly the main ones i.e Islam and Christianity as an agent in the context of the politics in Nigeria. This study uses qualitative and descriptive methodology. Using structural-functional theory and employing largely Rajeev Dhawan‘s analysis of constitutional secularism, we found that secular life and religion are pervasively entangled to the extent that official indifference cannot justify politically or constitutionally the indifference. Many official practices such as work-free days (Saturdays and Sundays), holidays (on Christmas, Idul fiṭr), churches and mosques in the state government houses and presidential villa clearly show that there is an engagement with religion. Islamic banking is one of the ways by which the economic aspect of Islam is practised; it does not violate section 10 of the Nigerian Constitution because it is not being financed directly or indirectly by the state funds. The conception of secularism in Nigeria is religious tolerance and equal treatment of all religious groups.